2021
DOI: 10.21203/rs.3.rs-544196/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Machine-learning Parsimonious Multivariable Predictive Model of Mortality Risk in Patients With Covid-19

Abstract: BackgroundThe COVID-19 pandemic is impressively challenging the healthcare system. Several prognostic models have been validated but few of them are implemented in daily practice. The objective of the study was to validate a machine-learning risk prediction model using easy-to-obtain parameters, potentially available at home, to help identifying patients with COVID-19 who are at higher risk of death.MethodsThe training cohort included all patients admitted to Fondazione Policlinico Gemelli with COVID-19 from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…The studies predominantly took place in inpatient settings (56%, n=17), with the emergency department (ED) (23%, n=7) and intensive care units (ICU) (20%, n=6) also represented. Within inpatient settings, nine studies examined general populations [20][21][22][23][24][25][26][27][28], and others focused on specific patient cohorts including those with central venous catheters (CVC) [30,31], systemic inflammatory response syndrome (SIRS) [29], and various other conditions. In ED settings, seven studies were identified [37][38][39][40][41][42][43], two of which addressed specific patient groups.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The studies predominantly took place in inpatient settings (56%, n=17), with the emergency department (ED) (23%, n=7) and intensive care units (ICU) (20%, n=6) also represented. Within inpatient settings, nine studies examined general populations [20][21][22][23][24][25][26][27][28], and others focused on specific patient cohorts including those with central venous catheters (CVC) [30,31], systemic inflammatory response syndrome (SIRS) [29], and various other conditions. In ED settings, seven studies were identified [37][38][39][40][41][42][43], two of which addressed specific patient groups.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…21,36 Although outside of the scope of this review, several groups are also utilizing strategies within the field of artificial intelligence to develop new prognostic models for COVID-19 that deserve further attention and may prove to be superior to current modeling paradigms in the biomedical sciences. [42][43][44][45] The use of artificial intelligence in developing prognostic models in COVID-19 is still in its infancy; more time and larger databases are required for machine learning algorithms to develop accurate models that may assist health care professionals.…”
Section: Other Scoresmentioning
confidence: 99%
“…Abbreviations: ABCS, age, biomarkers, clinical history, sex; ANDC, age, neutrophil-to-lymphocyte ratio, D-dimer, C-reactive protein; AST, aspartate transaminase; AUC, area under the curve; BUN, blood urea nitrogen; CKD-EPI, chronic kidney disease epidemiology collaboration; COPD, chronic obstructive pulmonary disease; COVID-19, coronavirus disease 2019; CRP; C-reactive protein; CT, computed tomography; eGFR, estimated glomerular filtration rate; GCS, Glasgow Coma Scale; Hgb, hemoglobin; hs-TNI, high sensitivity troponin; ICU, intensive care unit; LDH, lactate dehydrogenase; NEWS, national early warning system; NEWS2, national early warning system 2; WBC, white blood cells.Seminars in Respiratory and Critical Care Medicine Vol 44. No.…”
mentioning
confidence: 99%
“…This nonlinear system becomes even more complex with the emergence of new virus variants, the uncertain effect of vaccination on the human population (Sowa et al., 2021) and the heterogeneity of regional developmental levels. A well‐developed interpretable machine learning framework (Ayoub et al., 2021; Murri et al., 2021) may adapt to this complex scenario and provide reasonable interpretation and predictive capabilities, which are critical for a greater understanding of the mechanisms underlying the effectiveness of various COVID‐19 control measures. Ultimately, this will facilitate the development and implementation of targeted and precise prevention and control strategies for the ongoing COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%